2015
DOI: 10.1016/j.toxicon.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a panel of high affinity antibodies and development of a biosensor-based immunoassay for the detection of okadaic acid in shellfish

Abstract: Okadaic acid (OA) and its derivatives, DTX-1 and DTX-2, are marine biotoxins associated with diarrhetic shellfish poisoning. Routine monitoring of these toxins relies on the mouse bioassay. However, due to the technical unreliability and animal usage of this bioassay, there is always a need for convenient and reliable alternative assay methods. A panel of monoclonal antibodies against OA was generated and the most suitable was selected for biosensor-based assay development using surface plasmon resonance. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…One CRM‐DSP‐Mus‐c sample that contained OA, DTX‐1, and DTX‐2 was also used in the specificity experiment. In one study , the cross‐reactivity of the monoclonal antibody against OA was found to be 73% with DTX‐1, which confirmed its suitability for both OA and DTX‐1 detection. In our study, nonspecific binding with YTX, PTX‐2, and DTX‐1 was not detected.…”
Section: Resultsmentioning
confidence: 86%
“…One CRM‐DSP‐Mus‐c sample that contained OA, DTX‐1, and DTX‐2 was also used in the specificity experiment. In one study , the cross‐reactivity of the monoclonal antibody against OA was found to be 73% with DTX‐1, which confirmed its suitability for both OA and DTX‐1 detection. In our study, nonspecific binding with YTX, PTX‐2, and DTX‐1 was not detected.…”
Section: Resultsmentioning
confidence: 86%
“…It was rather sensitive and might be better than the sensitivity (IC 10 ) of most ic-ELISA methods (0.06–7.4 ng mL −1 in buffer, shown in Table S3†) reported previously. 8,9,40,41…”
Section: Resultsmentioning
confidence: 99%
“…56 It can monitor the surface property of the sensor, when the immobilized ligand is combined with the target molecule by biolayer interferometry technology in real time. 57 At this stage, there have been reports of the BLI sensors used on small molecule detection. 38,50 We performed a series of measurements on the newly developed BLI sensor in the concentration range of 40-600 nM to evaluate the feasibility and stability of the sensor (Fig.…”
Section: Bli Aptasensor For Dtx-1 Detectionmentioning
confidence: 99%
“…Reports on the OA aptasensor at this stage indicated that it had high specicity for OA, while it is unable to detect DTX-1. 57 Repeatability and specicity are essential for the aptasensor. In order to test the repeatability of the aptasensor, we executed repeated measurements on the 100 nM DTX-1 solution and collected the response.…”
Section: Bli Aptasensor For Dtx-1 Detectionmentioning
confidence: 99%